Community Leadership in a Dynamic Perspective: An Exploratory Study of Community Foundations in Hong Kong During the COVID-19 Pandemic - Han Ling; Gou Xinning (Nonprofit Policy Forum)
This study investigates the activities of three foundations in Hong Kong and their strategies for nurturing community leadership amid the COVID-19 pandemic (2020–2023). Employing a community leadership framework, we adopt an interpretive approach based on three case studies to address: How do foundations navigate crises like natural disasters and financial downturns from a community leadership perspective? This exploratory study builds on the existing community leadership framework to offer a dynamic understanding of how organizational attributes shape strategic initiatives during crises. We argue that philanthropic missions and fundraising capacities are key components for understanding the multidimensional nature of community leadership in times of crisis. With limited research on philanthropy in Hong Kong and Asia, this study offers insights into community leadership and the evolving dynamics of place-based philanthropy in uncertain times.